Práticas de prevenção de quedas de cuidadores de idosos e fatores associados - Mamani, Abigail Roxana Nina (2018)
The fall of the elderly is a public health problem that brings considerable implications for the elderly and your caregiver. This study aimed to analyze the practices of prevention of falls of the elderly carried out by informal caregivers and the associated factors. Analytical crosssectional study, developed in five units of the family health strategy in the northern region of the municipality of Cuiabá-MT, with 97 informal caregivers of seniors. These caregivers were selected by non-probability sampling from the criteria: be informal caregiver and elderly main, age less than 18 years. The data were collected in the households of the caregivers in the months of June to August 2017 through the interview with questionnaire prepared by researcher and validated by a Committee of 9 judges. The dependent variable of study is prevention of falls by the caregiver and the independent variables the demographic and socioeconomic characteristics, health conditions and the role of caregiver and elderly receiver related variables Watch. The data were organized in database with double typing followed by the descriptive analysis, bivariate and multiple using Poisson regression method to identify the factors associated with. Research approved by the Research Ethics Committee of the Hospital Julius Muller, opinion No 1,978,887 in 23/03/2017 and is linked to the Edict n 071/2013 PROCAD. Of 97 caregivers interviewed, the majority (72.2%) is between the ages of 40 and 69 years, (85.6%) is female, 47.4% are married or in a stable, 71.1% possesses 9 years or more of study, 60.9% receive 1 to 3 minimum wages from work, retirement and pension. In relation to the health of the caregiver, 40.2% auto evaluate assess your state of health as well, and 70.1% have health problems. Half (50.5%) of caregivers make regular use of drugs, 77.7% of 1 to 3 medicines. In relation to the characteristics of the aged care receiver more than half (57.8%) of seniors is aged 80 years or more, most (74.2%) has cognitive deficit, 40.2% have dependency modified with assistance of up to 25% and independence modified (25.8%) as Functional independence measurement (FIM). In relation to falls, 42.3% of seniors reported fall in the last 12 months, 90.7% have high risk of falls. Most (60.8%) of caregivers is the son/daughter, 73.2% reported not have previous experience and 44.4% serves for a time of 1 to 4 years. < The prevalence of falls prevention practices was 26.8% and was statistically significant association with the variables: years of study (p = 0.027). Finally, the prevalence of caregivers who practice falls prevention is low, caregivers with 0 to 8 years of study, marital status and with unfavorable attitudes showed a higher prevalence of nonpractice.